Method for detecting metal elements in perfluoropolymer

Through in-situ ash microwave digestion method and ICP-MS detection, the complexity and accuracy of fluoropolymer digestion and metal ion load testing are solved, and efficient and accurate metal element detection is achieved, suitable for high stability and resistance Corrosive perfluoropolymer.

CN119224104APending Publication Date: 2024-12-31WUHAN LVDONG HYDROGEN ENERGY TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411378408.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, the digestion of fluoropolymers and metal ion load testing methods have defects such as cumbersome steps, easy to lose components, high safety risks, high cost, low efficiency, and easy introduction of new impurities, making it difficult to accurately detect high stability and The content of metal elements in corrosion-resistant perfluoropolymers.

Method used

In-situ ash microwave digestion method is used to perform high-temperature ashing and microwave digestion in a quartz lined tube, and the metal element content is measured in combination with an inductively coupled plasma mass spectrometer (ICP-MS) to avoid component losses and impurities. Introduce, simplify operations and improve test accuracy.

Benefits of technology

It realizes the thorough digestion of high stability and corrosion-resistant perfluoropolymers and metal element detection, reduces sample loss and testing time, improves detection accuracy and efficiency, and is suitable for acid and alkali corrosion-resistant perfluoropolymers and related composites. Material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119224104A_ABST
    Figure CN119224104A_ABST
Patent Text Reader

Abstract

The invention discloses a method for detecting metal elements in a perfluoropolymer, which comprises the following steps: (1) adding a perfluoropolymer sample into a quartz lining tube for ashing to obtain the quartz lining tube filled with the sample after ashing; (2) adding a digestion solution into the quartz lining tube filled with the ashed sample, and then carrying out microwave digestion to obtain a digested liquid; (3) preparing the digested liquid to obtain a liquid to be detected; and measuring the content of the to-be-measured metal elements in the to-be-measured liquid by adopting an inductively coupled plasma mass spectrometer. According to the method, the high-stability and corrosion-resistant perfluoropolymer sample is subjected to in-situ ash content microwave digestion, then the inductively coupled plasma mass spectrometer is adopted to measure the content of the to-be-measured metal elements in the perfluoropolymer sample, component loss and introduction of new impurities are avoided, and the method has the advantages of being easy and convenient to operate, short in treatment time, more thorough in digestion, high in accuracy and the like. The test precision is high, the range of treatable samples is wide, and samples can be treated in batches.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials, and more specifically, to a method for detecting metal elements in perfluoropolymers. Background Technology

[0002] Proton exchange membrane fuel cell (PEMFC) modules widely utilize fluoropolymer materials. For example, perfluorosulfonic acid ion polymers (PFSI) are currently the mainstream commercial proton exchange membrane preparation materials, possessing excellent chemical stability, thermal stability, mechanical stability, and dimensional stability. Sulfonic acid branches, due to their fluorosulfonate ion clusters, exhibit excellent ion conductivity and are core components of fuel cells. Porous expanded polytetrafluoroethylene (ePTFE) membranes are often used as reinforcing layers for proton exchange membranes, thereby significantly improving the mechanical properties of the proton exchange membrane.

[0003] The detection of impurity elements in fluoropolymers is of great significance, especially the detection of metal element content in fluoropolymers. However, the high stability and high corrosion resistance of fluoropolymers mean that they are difficult to completely digest, making it impossible to quickly detect impurity elements and ion loadings using solution sample detection methods. This poses certain difficulties for product design, process development, and quality inspection.

[0004] Polymer digestion methods include ash separation, acid digestion, and microwave digestion. Ash separation involves calcining the polymer at high temperature to produce ash, which is then digested. This method can handle most polymers. Acid digestion involves heating the polymer directly in strong acids such as sulfuric acid or nitric acid, causing it to gradually dissolve. This method is simple to operate and suitable for polymers with poor stability and low corrosion resistance. Microwave digestion involves placing the polymer and digestion solution in a digestion vessel, where microwave heating of the digestion solution gradually digests the sample into a solution. This method is thorough and can handle most relatively stable polymers. However, acid digestion and microwave digestion cannot directly process highly corrosion-resistant polymers, such as polytetrafluoroethylene (PTFE). Ash separation has drawbacks such as difficulty in ash collection, cumbersome procedures, and significant sample loss during processing, leading to decreased accuracy in subsequent ion loading and impurity content tests.

[0005] Related technologies disclose the use of two or more combinations of concentrated nitric acid, concentrated sulfuric acid, concentrated hydrochloric acid, hydrogen peroxide, and hydrofluoric acid in a certain volume ratio as a digestion solution. The resin is mixed with the digestion solution, digested using microwave digestion, and the metal loading is then tested by inductively coupled plasma optical emission spectrometry (ICP-OES). This method is a typical microwave digestion method and can be used for the digestion of conventional resins such as polyethylene and polypropylene. However, it is ineffective for digesting fluoropolymers resistant to strong acids.

[0006] Current methods for digesting fluoropolymers and testing metal ion loading have drawbacks such as cumbersome procedures, easy loss of components, and high safety risks. Summary of the Invention

[0007] This invention is based on the inventor's discovery and understanding of the following facts and problems: Currently, the polymer ash separation method has defects such as difficulty in collecting ash, cumbersome steps, and serious sample loss during the processing, which leads to a decrease in the accuracy of subsequent ion loading and impurity content testing.

[0008] Inductively coupled plasma mass spectrometry (ICP-MS) features a wide dynamic linear range, low detection limit, and high sensitivity. However, due to its testing principle, ICP-MS can only test solution samples. This means that to analyze the metal element content in solid samples, they must be digested into a solution to fully release the analyte. However, the high stability and corrosion resistance of fluoropolymers make complete digestion difficult. Current methods for digesting fluoropolymers and determining metal ion loading suffer from drawbacks such as cumbersome procedures, easy component loss, high safety risks, high cost, long digestion time, low efficiency, and the potential introduction of new impurities.

[0009] This invention aims to at least partially solve one of the technical problems in related technologies. To this end, embodiments of this invention propose a method for detecting metal elements in perfluoropolymers. The method involves in-situ microwave digestion of highly stable, corrosion-resistant perfluoropolymer samples, followed by inductively coupled plasma mass spectrometry (ICP-MS) to measure the content of the target metal element in the perfluoropolymer sample. This method avoids component loss and the introduction of new impurities, is simple to operate, has a short processing time, provides more thorough digestion, offers high testing accuracy, can handle a wide range of samples, and allows for batch processing of samples.

[0010] This invention provides a method for detecting metal elements in perfluoropolymers, comprising the following steps:

[0011] (1) The perfluoropolymer sample was added to a quartz inner tube for ashing to obtain a quartz inner tube containing the ashing sample.

[0012] (2) Add digestion solution to the quartz inner tube containing the ashing sample, and then perform microwave digestion to obtain the digested liquid;

[0013] (3) The digested liquid is prepared to obtain the test solution; the content of the metal element to be tested in the test solution is determined by inductively coupled plasma mass spectrometry.

[0014] The advantages and technical effects of the method for detecting metal elements in perfluoropolymers in this invention are as follows: In-situ ash microwave digestion is performed on highly stable and corrosion-resistant perfluoropolymer samples, followed by inductively coupled plasma mass spectrometry to measure the content of the metal elements to be tested in the perfluoropolymer samples. This avoids component loss and the introduction of new impurities, is simple to operate, has a short processing time, provides more thorough digestion, has high testing accuracy, can handle a wide range of samples, and can process samples in batches.

[0015] In this invention, a wide range of samples can be processed. This invention is applicable to all acid and alkali resistant perfluoropolymers and related composite materials, including polytetrafluoroethylene, perfluorosulfonic acid resins, proton exchange membranes, and even composite materials or components containing perfluoropolymers, such as hydrogen fuel cell membrane electrodes.

[0016] In this invention, sample loss is low and testing accuracy is high. This invention uses a quartz-lined tube for in-situ ash-microwave digestion of perfluoropolymer samples. From high-temperature ashing to microwave digestion, the sample remains within the quartz-lined tube throughout the entire pretreatment process. Therefore, the entire pretreatment process does not involve ash collection or container transfer, avoiding component loss and the introduction of impurities. Furthermore, the quartz-lined tube prevents the introduction of other metallic element impurities that could contaminate the sample. The resulting digested liquid dissolves almost all the analyte metals in the sample, and the prepared test solution can be directly tested using ICP-MS. This invention uses ICP-MS, which has higher accuracy than ICP-OES, to determine the content of metal ions in the sample. The use of ICP-MS allows for detection limits of metal elements down to the ppt level. The method of this invention significantly avoids the loss of effective components, accurately testing the content of metal elements in perfluoropolymer samples and quantitatively detecting trace impurity elements.

[0017] In this invention, the cost is low and the efficiency is high. The method of this invention only involves two commonly used instruments: an ashing instrument such as a muffle furnace and a microwave digester. ICP-MS can be used to complete the digestion and testing of the sample, without the need for special equipment. Microwave digestion allows the digestion process to be completed in a single step, eliminating the need for the two digestion steps of nitration followed by aqua regia acidification in traditional acid digestion methods, thus greatly saving processing time. From sample ashing to ICP-MS testing, the entire process can be completed within one day, and samples can be processed in batches. Compared with methods such as high-temperature dynamic digestion of fluorine gas and oxygen bomb combustion, the method of this invention overcomes the disadvantages of complex equipment, high cost, easy introduction of impurity ions during processing, and easy loss of ash during transfer and collection. Compared with traditional ash-digestion methods and strong acid digestion methods, the method of this invention is simple to operate, has a short processing time, more thorough digestion, high testing accuracy, and covers a wide range of samples. It can digest highly corrosion-resistant perfluoropolymers such as polytetrafluoroethylene, and can also process membrane electrode assemblies for hydrogen fuel cells containing proton exchange membranes.

[0018] In some embodiments, in step (1), the ashing temperature is 800–1000°C;

[0019] And / or, the ashing time is 2-4 hours.

[0020] In some embodiments, in step (1), the perfluoropolymer sample comprises at least one of polytetrafluoroethylene, perfluorosulfonic acid resin, perfluorosulfonic acid proton exchange membrane, and hydrogen fuel cell membrane electrode assembly.

[0021] And / or, weigh 10–50 mg of the perfluoropolymer sample;

[0022] And / or, measure 1–50 cm 2 The perfluoropolymer sample.

[0023] In some embodiments, in step (2), the digestion solution includes concentrated nitric acid, concentrated sulfuric acid, and perchloric acid.

[0024] In some embodiments, the volume ratio of concentrated nitric acid, concentrated sulfuric acid, and perchloric acid is 1 to 4:1:1.

[0025] In some embodiments, in step (2), the temperature of microwave digestion is 200–250°C;

[0026] And / or, the microwave digestion time is 60–90 min.

[0027] In some embodiments, in step (2), the microwave digestion is performed using a digestion vessel; a loading solution is added to the digestion vessel, and then the quartz liner tube containing the ashed sample is placed into the digestion vessel containing the loading solution. Digestion solution is added to the quartz liner tube containing the ashed sample, and then microwave digestion is performed to obtain the digested liquid; preferably, the loading solution includes dilute nitric acid.

[0028] In some embodiments, in step (3), the digested liquid is transferred to a volumetric flask and diluted to volume to obtain the test solution;

[0029] And / or, before determining the content of the metal element to be tested in the test solution, a standard solution of the metal element to be tested is prepared, a standard curve of the metal element to be tested is established, and then the content of the metal element to be tested in the test solution is determined by inductively coupled plasma mass spectrometry.

[0030] In some embodiments, in step (3), the metal element to be tested includes at least one of a main group metal element or a transition metal element.

[0031] In some embodiments, in step (3), after determining the content of the metal element to be tested in the test solution, the mass fraction of the metal element to be tested in the perfluoropolymer sample is obtained by conversion according to formula (1):

[0032]

[0033] Wherein, the metal element to be tested is the metal element X, ω X c represents the mass fraction of the metal element X to be tested in the perfluoropolymer sample. X The concentration of the metal element X to be tested in the test solution is given in mg·L. -1 V is the volume of the test solution in mL, and m0 is the mass of the perfluoropolymer sample in mg.

[0034] And / or, in step (3), after determining the content of the metal element to be tested in the test solution, the content of the metal element to be tested in the perfluoropolymer sample is calculated according to formula (2):

[0035]

[0036] Wherein, the metal element to be tested is metal element X, α X This is the planar content of the metal element X to be tested in the perfluoropolymer sample, expressed in mg·cm⁻¹. -2 c X The concentration of the metal element X to be tested in the test solution is given in mg·L. -1 V represents the volume of the test solution in mL, and S0 represents the area of ​​the perfluoropolymer sample in cm². 2 . Attached Figure Description

[0037] Figure 1 This is a schematic diagram of the digestion process using a quartz-lined tube containing an ashing sample.

[0038] Figure 2 This is the standard curve for ICP-MS testing of Pt.

[0039] Figure 3 This is the standard curve for ICP-MS testing of Ce element.

[0040] Figure label:

[0041] Digestion vessel 1, quartz liner tube 2, ashed sample 3, digestion solution 4, loading solution 5. Detailed Implementation

[0042] Embodiments of the present invention are described in detail below, examples of which are illustrated in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.

[0043] An embodiment of the present invention provides a method for detecting metal elements in perfluoropolymers, comprising the following steps:

[0044] (1) The perfluoropolymer sample was added to a quartz inner tube for ashing to obtain a quartz inner tube containing the ashing sample.

[0045] (2) Add digestion solution to the quartz inner tube containing the ashing sample, and then perform microwave digestion to obtain the digested liquid;

[0046] (3) The digested liquid is prepared to obtain a test solution; the content of the metal element to be tested in the test solution is determined by inductively coupled plasma mass spectrometry; optionally, the content of the metal element to be tested in the test solution is the concentration of the metal element to be tested in the test solution.

[0047] The method for detecting metal elements in perfluoropolymers according to embodiments of the present invention involves in-situ ash microwave digestion of highly stable and corrosion-resistant perfluoropolymer samples, followed by inductively coupled plasma mass spectrometry to measure the content of the metal element to be tested in the perfluoropolymer sample. This method avoids component loss and the introduction of new impurities, is simple to operate, has a short processing time, provides more thorough digestion, has high testing accuracy, can handle a wide range of samples, and can process samples in batches.

[0048] In this invention, a wide range of samples can be processed. This invention is applicable to all acid and alkali resistant perfluoropolymers and related composite materials, including polytetrafluoroethylene, perfluorosulfonic acid resins, proton exchange membranes, and even composite materials or components containing perfluoropolymers, such as hydrogen fuel cell membrane electrodes.

[0049] In this invention, sample loss is low and testing accuracy is high. This invention uses a quartz-lined tube for in-situ ash-microwave digestion of perfluoropolymer samples. From high-temperature ashing to microwave digestion, the sample remains within the quartz-lined tube throughout the entire pretreatment process. Therefore, the entire pretreatment process does not involve ash collection or container transfer, avoiding component loss and the introduction of impurities. Furthermore, the quartz-lined tube prevents the introduction of other metallic element impurities that could contaminate the sample. The resulting digested liquid dissolves almost all the analyte metals in the sample, and the prepared test solution can be directly tested using ICP-MS. This invention uses ICP-MS, which has higher accuracy than ICP-OES, to determine the content of metal ions in the sample. The use of ICP-MS allows for detection limits of metal elements down to the ppt level. The method of this invention significantly avoids the loss of effective components, accurately testing the content of metal elements in perfluoropolymer samples and quantitatively detecting trace impurity elements.

[0050] In this invention, the cost is low and the efficiency is high. The method of this invention only involves two commonly used instruments: an ashing instrument such as a muffle furnace and a microwave digester. ICP-MS can be used to complete the digestion and testing of the sample, without the need for special equipment. Microwave digestion allows the digestion process to be completed in a single step, eliminating the need for the two digestion steps of nitration followed by aqua regia acidification in traditional acid digestion methods, thus greatly saving processing time. From sample ashing to ICP-MS testing, the entire process can be completed within one day, and samples can be processed in batches. Compared with methods such as high-temperature dynamic digestion of fluorine gas and oxygen bomb combustion, the method of this invention overcomes the disadvantages of complex equipment, high cost, easy introduction of impurity ions during processing, and easy loss of ash during transfer and collection. Compared with traditional ash-digestion methods and strong acid digestion methods, the method of this invention is simple to operate, has a short processing time, more thorough digestion, high testing accuracy, and covers a wide range of samples. It can digest highly corrosion-resistant perfluoropolymers such as polytetrafluoroethylene, and can also process membrane electrode assemblies for hydrogen fuel cells containing proton exchange membranes.

[0051] In some embodiments, in step (1), the perfluoropolymer sample means a sample containing a perfluoropolymer; optionally, the perfluoropolymer sample includes at least one of polytetrafluoroethylene, perfluorosulfonic acid resin, perfluorosulfonic acid proton exchange membrane, and hydrogen fuel cell membrane electrode assembly; optionally, the polytetrafluoroethylene includes bulk polytetrafluoroethylene (PTFE) or expanded polytetrafluoroethylene membrane (ePTFE); the perfluorosulfonic acid proton exchange membrane includes at least one of perfluorosulfonic acid proton exchange membrane without reinforcement layer or ePTFE-reinforced perfluorosulfonic acid proton exchange membrane; the hydrogen fuel cell membrane electrode assembly includes a perfluorosulfonic acid proton exchange membrane.

[0052] In some embodiments, in step (1), 10–50 mg of the perfluoropolymer sample is weighed, specifically, for example, 10 mg, 20 mg, 30 mg, 40 mg, or 50 mg; and / or, 1–50 cm³ is measured. 2 The perfluoropolymer sample, specifically, for example, 1 cm 2 4cm 2 9cm 2 16cm 2 25cm 2 30cm 2 36cm 2 40cm 2 50cm 2 In this embodiment of the invention, the mass of bulk samples is generally measured, while the size or mass of membrane samples can be measured as needed.

[0053] In some embodiments, in step (1), the perfluoropolymer sample is shredded or cut into small pieces before ashing; optionally, plastic scissors are used.

[0054] In some embodiments, in step (1), the ashing temperature is 800–1000°C, specifically, for example, 800°C, 850°C, 900°C, 950°C, and 1000°C; the ashing time is 2–4 hours, specifically, for example, 2 hours, 3 hours, and 4 hours. In this embodiment of the invention, all perfluoropolymer samples will ashing at an ashing temperature of 800–1000°C.

[0055] In some embodiments, in step (1), the ashing is performed using a muffle furnace, the perfluoropolymer sample is added to a quartz inner liner tube, and then the quartz inner liner tube containing the perfluoropolymer sample is placed in the muffle furnace; optionally, a ceramic crucible rack is used to fix the quartz inner liner tube or the quartz inner liner tube is placed in a crucible to prevent it from tipping over; optionally, the quartz inner liner tube is removed after the muffle furnace temperature has cooled down.

[0056] In some embodiments, in step (2), the digestion solution includes concentrated nitric acid, concentrated sulfuric acid, and perchloric acid; optionally, the volume ratio of the concentrated nitric acid, concentrated sulfuric acid, and perchloric acid is 1 to 4:1:1, specifically, for example, 1:1:1, 2:1:1, 3:1:1, 4:1:1; optionally, the amount of digestion solution added is adjusted according to the amount of sample and the capacity of the quartz liner tube. In a specific embodiment, the volumes of the concentrated nitric acid, concentrated sulfuric acid, and perchloric acid are 2 mL each; optionally, the mass percentage concentration of the concentrated nitric acid is 68%, and the purity is analytical grade; the mass percentage concentration of the concentrated sulfuric acid is 98%, and the purity is analytical grade; the mass percentage concentration of the perchloric acid is 70%, and the purity is analytical grade.

[0057] In this embodiment of the invention, the digestion solution includes concentrated nitric acid, concentrated sulfuric acid, and perchloric acid in a volume ratio of 1 to 4:1:1. This ensures that the digestion system reaches the required digestion temperature while also allowing the strong oxidizing properties of the digestion solution to be fully and safely digested at this temperature. Without concentrated nitric acid, the digestion solution temperature may be too high, damaging the digestion vessel; without concentrated sulfuric acid, the temperature of the digestion solution will be difficult to raise above 200°C, hindering the complete oxidation and digestion of the ash; without perchloric acid, the oxidizing power of the digestion solution is insufficient, easily leading to incomplete sample digestion.

[0058] In some embodiments, in step (2), the microwave digestion is performed using a microwave digester.

[0059] In some embodiments, in step (2), the microwave digestion temperature is 200-250°C, specifically, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C; and the microwave digestion time is 60-90 min, specifically, for example, 60 min, 70 min, 80 min, 90 min.

[0060] In this embodiment of the invention, the high temperature environment exceeding 200°C during the digestion process allows the strong oxidizing properties of perchloric acid and concentrated nitric acid to fully oxidize components such as carbon and metal oxides in the ash, thereby fully oxidizing and digesting the ash and releasing the metal ions therein into the digestion solution. The released metal components react directly with the digestion solution to generate easily soluble ionic forms, which facilitates subsequent ion detection and further improves the testing accuracy.

[0061] In some embodiments, such as Figure 1 As shown, in step (2), the microwave digestion is performed using digestion vessel 1;

[0062] Optionally, a loading solution 5 is added to the digestion vessel 1, and then the quartz inner tube 2 containing the ashed sample 3 is placed into the digestion vessel 1 containing the loading solution 5. Digestion solution 4 is added to the quartz inner tube 2 containing the ashed sample 3, and then microwave digestion is performed to obtain the digested liquid.

[0063] Optionally, the loading solution 5 includes dilute nitric acid; optionally, the mass fraction of the dilute nitric acid is 5-10%, specifically, for example, 5%, 6%, 7%, 8%, 9%, 10%; the amount of loading solution 5 added is adjusted according to the amount of sample, the capacity of the quartz liner tube, and the size of the digestion vessel 1. Optionally, the amount of loading solution 5 added is 5-10 mL, specifically, for example, 5 mL, 6 mL, 7 mL, 8 mL, 9 mL, 10 mL;

[0064] Optionally, the digestion vessel 1 is a polytetrafluoroethylene digestion vessel; optionally, the capacity of the digestion vessel 1 is 50 mL; the digestion vessel 1 is clean and dry.

[0065] In this embodiment of the invention, after the perfluoropolymer sample is ashed, the quartz-lined tube is directly placed into the digestion vessel for digestion. The role of the loading solution is to maintain the temperature of the system inside the quartz-lined tube and the temperature inside the digestion vessel at the same level, so that the temperature sensor of the microwave digester can more accurately detect the temperature inside the vessel, control the microwave digestion temperature, and prevent the digestion vessel from being burned out due to excessive microwave heating temperature inside the quartz-lined tube during microwave digestion.

[0066] In some embodiments, an acid removal operation can be performed after digestion is completed, depending on actual needs. In this invention, acid removal is not required; the quartz inner liner tube can be removed directly and the digested liquid can be transferred to a volumetric flask.

[0067] In some embodiments, in step (3), the digested liquid is prepared to obtain a test solution; optionally, the digested liquid is diluted and brought to volume to obtain a test solution; optionally, the digested liquid is transferred to a volumetric flask and brought to volume to obtain a test solution; optionally, the digested liquid is transferred to a volumetric flask, diluted and brought to volume to obtain a test solution; optionally, the volumetric flask has a capacity of 50-1000 mL, specifically, for example, 50 mL, 100 mL, 250 mL, 500 mL, 1000 mL; optionally, the diluent and volume-setting solvent are pure water.

[0068] In some embodiments, in step (3), before determining the content of the metal element to be tested in the test solution, a standard solution of the metal element to be tested is prepared, a standard curve of the metal element to be tested is established, and then the content of the metal element to be tested in the test solution is determined by inductively coupled plasma mass spectrometry.

[0069] Optionally, a standard solution of the metal element to be tested is prepared, and the standard solution is measured by inductively coupled plasma mass spectrometry to establish a standard curve of the metal element to be tested.

[0070] Optionally, the standard curve is a signal ratio-concentration standard curve; wherein, the signal ratio is the ratio of the signal intensity of the metal element to be measured to the signal intensity of the internal standard element, i.e., the signal ratio; and the concentration is the concentration of the standard solution.

[0071] Optionally, a series of standard solutions of the metal element to be tested are prepared, wherein the concentrations of the standard solutions of the metal element to be tested form a gradient; optionally, the concentration levels of the standard solutions of the metal element to be tested are set according to the concentration range of the metal element to be tested in the test solution.

[0072] Optionally, the standard solution uses dilute nitric acid as a matrix. More preferably, the mass percentage of dilute nitric acid is 1-10%, specifically, for example, 1%, 2%, 5%, 8%, or 10%.

[0073] In some embodiments, in order to correct the drift of the mass number signal of the ICP-MS instrument, an internal standard element solution is usually introduced at the same time as the test sample during ICP-MS detection. Optionally, the concentration of the internal standard element solution is 1 to 5 ppm, and the internal standard element should be selected from elements with a mass number close to that of the analyte. For example, Bi is usually selected as the internal standard element for Pt, and Tb is selected as the internal standard element for Ce.

[0074] In some embodiments, in step (3), the metal element to be tested includes at least one of a main group metal element or a transition metal element; optionally, the metal element to be tested does not include a radioactive metal element or a highly corrosion-resistant metal element; optionally, the metal element to be tested includes at least one of Na, K, Cr, Mn, Fe, Co, Ni, Cu, and Pt. In this embodiment of the invention, the metal element to be tested is an element contained in the perfluoropolymer sample or an impurity element.

[0075] In some embodiments, in step (3), after determining the content of the metal element to be tested in the test solution, the mass fraction of the metal element to be tested in the perfluoropolymer sample is obtained by conversion according to formula (1):

[0076]

[0077] Wherein, the metal element to be tested is the metal element X, ω X c represents the mass fraction of the metal element X to be tested in the perfluoropolymer sample. X The concentration of the metal element X to be tested in the test solution is given in mg·L. -1 (ppm), V is the volume of the test solution in mL, and m0 is the mass of the perfluoropolymer sample in mg.

[0078] In some embodiments, in step (3), after determining the content of the metal element to be tested in the test solution, the content of the metal element to be tested in the perfluoropolymer sample is calculated according to formula (2):

[0079]

[0080] Wherein, the metal element to be tested is metal element X, α X This is the planar content of the metal element X to be tested in the perfluoropolymer sample, expressed in mg·cm⁻¹. -2 c XThe concentration of the metal element X to be tested in the test solution is given in mg·L. -1 (ppm), V is the volume of the test solution in mL, and S0 is the area of ​​the perfluoropolymer sample in cm². 2 Optionally, the unit of planar content can also be converted to mg·m³ as needed. -2 .

[0081] The present invention will now be described with reference to specific embodiments. It should be noted that these embodiments are merely descriptive and do not limit the present invention in any way.

[0082] Example 1

[0083] A method for detecting the Pt elemental impurity content in polytetrafluoroethylene (PTFE) bulk materials, comprising the following steps:

[0084] (1) Use plastic scissors to take 11.64 mg of polytetrafluoroethylene sample, cut it into small pieces, and put it into the quartz inner liner tube that is matched with the digestion vessel; put the quartz inner liner tube into the muffle furnace and heat it to 1000℃ for 2 hours to ashed the sample.

[0085] (2) Prepare a clean digestion vessel, add 6 mL of 5% dilute nitric acid as a loading solution, and put the quartz liner tube containing the ashing sample into the digestion vessel.

[0086] (3) Add digestion solution to the quartz inner liner tube inside the digestion vessel. The digestion solution is a mixed acid consisting of 2 mL concentrated nitric acid, 2 mL perchloric acid and 2 mL concentrated sulfuric acid. Place the digestion vessel on the rotor of the microwave digestion instrument. Use the microwave digestion instrument to microwave digest the sample: place the rotor into the sample chamber of the digestion instrument, set the digestion temperature to 250℃ and the digestion time to 90 min, and obtain the digested liquid.

[0087] (4) After microwave digestion, remove the quartz inner tube, transfer the digested liquid in the quartz inner tube to a 100mL volumetric flask, and dilute to 100mL with pure water to complete the sample preparation and obtain the test solution.

[0088] (5) Using the national standard platinum elemental solution (10 μg / mL) as the matrix, standard solutions with concentrations of 5, 10, 15, 20, and 25 ppb were prepared; the standard solutions were measured using ICP-MS to establish a standard curve for platinum elemental solution, as shown below. Figure 2 As shown;

[0089] (6) The Pt element content in the test solution was detected by ICP-MS, and the internal standard element was selected. 209 Bi was used to obtain the mass concentration data of Pt element in the test liquid, and the element content of Pt in polytetrafluoroethylene block was calculated according to formula (1).

[0090] Table 1 shows the ICP-MS test results after PTFE digestion. It can be seen that the content of Pt, as an impurity, in the solution is extremely low—less than 1 ppb (μg·L⁻¹). -1 This translates to a Pt mass fraction of 0.000133% in the polytetrafluoroethylene sample. Due to the use of ICP-MS and the absence of new impurities introduced during sample processing, the detection limit and sensitivity for quantitative elemental analysis in samples are significantly improved compared to ICP-OES.

[0091] Table 1. Test results of Pt element in PTFE.

[0092]

[0093] Example 2

[0094] A method for detecting the Pt elemental impurity content in expanded polytetrafluoroethylene (ePTFE) film includes the following steps:

[0095] (1) Use plastic scissors to take 10.44 mg of expanded polytetrafluoroethylene film sample, fold it and put it into the quartz inner liner tube that is matched with the digestion vessel; put the quartz inner liner tube into the muffle furnace and heat it to 1000℃ for 2 hours to ashed the sample.

[0096] (2) Prepare a clean digestion vessel, add 6 mL of 5% dilute nitric acid as a loading solution, and put the quartz liner tube containing the ashing sample into the digestion vessel.

[0097] (3) Add digestion solution to the quartz inner liner tube inside the digestion vessel. The digestion solution is a mixed acid consisting of 2 mL concentrated nitric acid, 2 mL perchloric acid and 2 mL concentrated sulfuric acid. Place the digestion vessel on the rotor of the microwave digestion instrument. Use the microwave digestion instrument to microwave digest the sample: place the rotor into the sample chamber of the digestion instrument, set the digestion temperature to 250℃ and the digestion time to 90 min, and obtain the digested liquid.

[0098] (4) After microwave digestion, remove the quartz inner tube, transfer the digested liquid in the quartz inner tube to a 100mL volumetric flask, and dilute to 100mL with pure water to complete the sample preparation and obtain the test solution.

[0099] (5) Using the national standard platinum elemental solution (10 μg / mL) as the matrix, standard solutions with concentrations of 5, 10, 15, 20, and 25 ppb were prepared; the standard solutions were measured using ICP-MS to establish a standard curve for platinum elemental solution, as shown below. Figure 2 As shown;

[0100] (6) The Pt element content in the test solution was detected by ICP-MS, and the internal standard element was selected.209 Bi was used to obtain the mass concentration data of Pt element in the test solution, and the elemental content of Pt in ePTFE was calculated according to formula (1). The ICP-MS test results are shown in Table 2.

[0101] Table 2 shows the test results of Pt element in ePTFE.

[0102]

[0103] Example 3

[0104] A type of ePTFE-enhanced perfluorosulfonic acid proton exchange membrane composite membrane (Ce addition amount of 50 mg·m³) -2 The method for detecting the Ce element content in a sample includes the following steps:

[0105] (1) Use plastic scissors to take a 5cm×5cm proton exchange membrane, cut it into pieces, and put it into the quartz inner liner tube that matches the digestion vessel; put the quartz inner liner tube into the muffle furnace and heat it to 1000℃ for 2 hours to ashed the sample.

[0106] (2) Prepare a clean digestion vessel, add 6 mL of 5% dilute nitric acid as a loading solution, and put the quartz liner tube containing the ashing sample into the digestion vessel.

[0107] (3) Add 2 mL of concentrated nitric acid, 2 mL of perchloric acid and 2 mL of concentrated sulfuric acid to the quartz liner tube inside the digestion vessel as digestion solution, and place the digestion vessel on the 20-position SVT rotor; use a microwave digester to digest at 250℃ for 90 min to obtain the digested liquid;

[0108] (4) After microwave digestion, remove the quartz inner tube, transfer the digested liquid in the quartz inner tube to a 100mL volumetric flask, dilute to volume with pure water, complete the sample preparation, and obtain the test solution.

[0109] (5) Using the national standard material Ce elemental solution (1000 ppm), with 5% dilute nitric acid as the matrix, standard solutions with concentrations of 0.5, 1, 1.5, 2, and 2.5 ppm were prepared; the standard solutions were measured using ICP-MS to establish a standard curve for Ce elemental analysis, as shown below. Figure 3 As shown;

[0110] (6) The Ce element content in the test solution was detected by ICP-MS, and the internal standard element was selected. 159 Tb was used to obtain the mass concentration data of Ce element in the test solution. The element content of Ce in the proton exchange membrane was calculated according to formula (2). The test results are shown in Table 3.

[0111] Comparative Example 1

[0112] A type of ePTFE-enhanced perfluorosulfonic acid proton exchange membrane composite membrane (Ce addition amount of 50 mg·m³) -2 The method for detecting the Ce element content in a sample includes the following steps:

[0113] (1) Using plastic scissors, take a 5cm×5cm proton exchange membrane identical to that in Example 3, cut it into pieces, and put it into a clean digestion vessel; add 2mL of concentrated nitric acid, 2mL of perchloric acid, and 2mL of concentrated sulfuric acid to the digestion vessel as digestion solution, and place the digestion vessel on a 20-position SVT rotor; use a microwave digestion apparatus to digest at 250℃ for 90min to obtain the digested liquid, and transfer the digested liquid to a 100mL volumetric flask and make up to volume to obtain the test solution;

[0114] (2) The Ce element content in the test solution was detected by ICP-MS, and the test results are shown in Table 3.

[0115] Table 3. Ce element test results in samples from Comparative Example 1 and Example 3.

[0116]

[0117] In Comparative Example 1, after digestion, the digestion vessel was examined and found to contain incompletely digested white flakes, which may be ePTFE components in the ePTFE-reinforced perfluorosulfonic acid proton exchange membrane. In contrast, the liquid after ash digestion of the sample in Example 3 was a clear solution, indicating that the method in Example 3 can thoroughly digest the perfluoropolymer sample. According to the results shown in Table 3, the Ce element content measured in Example 3 was higher than that measured in Comparative Example 1 and closer to the theoretical value, demonstrating higher accuracy. This is because Comparative Example 1 did not undergo ashing treatment and directly performed microwave digestion, resulting in incompletely digested perfluorosulfonic acid components in the perfluoropolymer sample, or the undigested ePTFE adsorbing some Ce, leading to incomplete release of the effective components. Example 3, using an in-situ ash-microwave digestion method, can effectively digest the perfluoropolymer components, fully expose the Ce element in the sample, and has minimal loss during processing, resulting in higher accuracy.

[0118] Comparative Example 2

[0119] A type of ePTFE-enhanced perfluorosulfonic acid proton exchange membrane composite membrane (Ce addition amount of 90 mg·m³) -2 The method for detecting Ce element content in samples involves dividing the samples into three groups:

[0120] The detection method for the first group of samples is the same as that in Example 3.

[0121] The detection method for the second group of samples is the same as that in Example 3, except that the temperature of microwave digestion in step (3) is 180°C.

[0122] The detection method for the third group of samples is the same as that in Example 3. The difference is that in step (3), the microwave digestion step is cancelled, and instead, 2 mL of concentrated nitric acid, 2 mL of perchloric acid and 2 mL of concentrated sulfuric acid are added to the quartz inner tube containing the ashing sample as a digestion solution. The sample is soaked at room temperature for 90 min to obtain the digested liquid.

[0123] Table 4. Ce element test results in Comparative Example 2 sample

[0124]

[0125] In Comparative Example 2, the test results of the first group of samples were closest to the theoretical values. The Ce content in the second group of samples decreased compared to the first group, while the Ce content in the third group was undetectable by the instrument (the instrument gave a concentration of 0.000 ppm). This is because the digestion of the ashing samples depends on the digestion temperature. Higher temperatures are more conducive to ash digestion. During digestion, temperatures exceeding 200℃ allow the strong oxidizing properties of perchloric acid and concentrated nitric acid to fully oxidize carbon, metal oxides, and other components in the ash, releasing metal ions into the digestion solution. The released metal components react directly with the digestion solution to generate easily soluble ionic forms, facilitating subsequent ion detection and further improving test accuracy. In the second group of samples, the microwave digestion temperature was below 200℃, resulting in insufficient oxidation and digestion after ashing. In the third group of samples, the digestion solution at room temperature could not digest the ashing samples, both of which are unfavorable for the detection of metal elements in the perfluoropolymer samples. The detection method in this invention uses microwave digestion at 200℃~250℃, which ensures complete ash digestion. In a strong acid environment, most metal elements can dissolve in the ash, thus improving the accuracy of ICP-MS elemental testing.

[0126] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0127] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.

Claims

1. A method for detecting metal elements in perfluoropolymers, characterized in that: The following steps are involved: (1) adding a perfluoropolymer sample into a quartz lined tube for ashing to obtain a quartz lined tube containing the ashed sample; (2) adding a digestion solution into the quartz lined tube containing the ashed sample, and then performing microwave digestion to obtain a digested liquid; (3) preparing the digested liquid to obtain a test liquid; and determining the content of the metal element in the test liquid by using an inductively coupled plasma mass spectrometer.

2. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (1), the ashing temperature is 800-1000° C.; And / or, the ashing time is 2-4h.

3. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (1), the perfluoropolymer sample comprises at least one of polytetrafluoroethylene, perfluorosulfonic acid resin, perfluorosulfonic acid proton exchange membrane, and hydrogen fuel cell membrane electrode assembly; and / or, weighing 10 to 50 mg of the perfluoropolymer sample; And / or, measure 1 to 50 cm 2 of the perfluoropolymer sample.

4. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (2), the digestion solution includes concentrated nitric acid, concentrated sulfuric acid and perchloric acid.

5. The method for detecting metal elements in perfluoropolymers according to claim 4, characterized in that: The volume ratio of the concentrated nitric acid, concentrated sulfuric acid and perchloric acid is 1-4:1:

1.

6. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (2), the temperature of the microwave digestion is 200-250°C; And / or, the microwave digestion time is 60 to 90 minutes.

7. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (2), the microwave digestion adopts a digestion tank; a loading solution is added into the digestion tank, and then the quartz lined tube containing the ashed sample is placed into the digestion tank containing the loading solution, and the digestion solution is added into the quartz lined tube containing the ashed sample, and then microwave digestion is performed to obtain a digested liquid; preferably, the loading solution includes dilute nitric acid.

8. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (3), the digested liquid is transferred to a volumetric flask and the test liquid is obtained after constant volume; And / or, before determining the content of the metal element to be measured in the test liquid, a standard solution of the metal element to be measured is prepared, a standard curve of the metal element to be measured is established, and then the content of the metal element to be measured in the test liquid is determined using an inductively coupled plasma mass spectrometer.

9. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (3), the metal element to be detected includes at least one of a main group metal element or a transition metal element.

10. The method for detecting metal elements in perfluoropolymers according to claim 1, characterized in that: In the step (3), after determining the content of the metal element to be measured in the test liquid, the mass fraction of the metal element to be measured in the perfluoropolymer sample is obtained by conversion according to formula (1): Wherein, the metal element to be measured is the metal element to be measured X, ω X is the mass fraction of the metal element X to be measured in the perfluoropolymer sample, c X is the concentration of the metal element X in the test solution, in mg·L -1 , V is the volume of the liquid to be tested, in mL, m0 is the mass of the perfluoropolymer sample, in mg; And / or, in the step (3), after determining the content of the metal element to be measured in the test liquid, convert it according to formula (2) to obtain the planar content of the metal element to be measured in the perfluoropolymer sample: Wherein, the metal element to be detected is the metal element to be detected X, α X is the planar content of the metal element X to be measured in the perfluoropolymer sample, in mg cm -2 , c X is the concentration of the metal element X in the test solution, in mg·L -1 , V is the volume of the test liquid, in mL, S0 is the area of ​​the perfluoropolymer sample, in cm 2 .

Citation Information

Cited By

  • Low-temperature separation and sampling process for metal elements in fluorine-containing polymer

    CN120869742A